CARBONATED PERIDOTITE XENOLITHS FROM SPITSBERGEN: IMPLICATIONS FOR TRACE ELEMENT SIGNATURE OF MANTLE CARBONATE METASOMATISM - Ionov D.A.; O'Reilly S.Y.; Dupuy C.; Kopylova M.G.; Genshaft Y.S. (My University, 1993)
Peridotite xenoliths from basaltic volcanics in NW Spitsbergen contain carbonates of mantle origin. These occur as pockets of granular dolomite (Mg# 0.95–0.99) accompanied by fine-grained olivine and Al,Cr,Ti-rich clinopyroxene apparently produced by reaction of carbonate-rich fluids with the primary mineral assemblage of coarse spinel peridotites. Accessory apatite occurs in one sample. Most commonly, however, the Spitsbergen xenoliths contain patches and veins of quenched carbonate and silicate melts [1,2]. Our observations suggest that the mantle carbonates melted shortly before or during the transport of the xenoliths to the surface, which also triggered local melting in the peridotites to produce a Na,Al-rich silicate glass.Four carbonate-bearing peridotite xenoliths were acid leached and the leachates, the residues after leaching and the bulk rocks were analysed for 25 trace elements by ICP-MS. The trace element inventory of the leachates is dominated by dissolved carbonate material. The leachates, and the bulk peridotites, show marked enrichment in LREE, Sr, Ba and Rb and are relatively depleted in Zr, Hf, Nb and Ta. In-situ analyses by proton microprobe show very high contents of Sr in clinopyroxenes, primary carbonates and accessory apatite; the apatite is also very rich in LREE, U, Th and Br. Relative enrichment in LREE and Sr over HREE and HFSE appears to be characteristic of mantle carbonates and carbonate-bearing peridotites. High Sr/Sm, Sm/Hf, La/Nb, Zr/Hf and Nb/Ta ratios in mantle peridotites (including basalt source regions) may be a signature of carbonate-related metasomatism.